Performance Evaluation of AODV and DSR Protocols in MANET (International Journal of Engineering and Computer Science, 2015)
MANETs are being widely used and it is the technology that is attracting a large variety of applications. Routing inMANETs is considered a challenging task due to the unpredictable changes in the network topology, resulting from the random andfrequent movement of the nodes and due to the absence of any centralized control. Efficient routing protocols can provide significantbenefits to mobile Ad-Hoc networks in terms of both performance and reliability. In this paper, we evaluate the performance of tworeactive routing protocols, Ad hoc On demand Distance Vector (AODV) and Dynamic Source Routing (DSR). The major goal of thisstudy is to analyze the performance of well known MANETs routing protocol in random mobility case. Hence it becomes important tostudy the impact of mobility on the performance of these routing protocols. The simulation has done in NS-2 simulator and theperformance is analyzed with respect to performance matrices like Average End-to-End Delay, Normalized Routing Load (NRL),Packet Delivery Fraction (PDF), and Throughput and also measures the performance of TCP and UDP packets. Simulation resultsverify that AODV gives better performance as compared to DSR